Analysis of Dispute Resolution Over Control of Forest Areas into Oil Palm Plantations - Siahaan, David Pandapotan; Anggusti, Martono; Siregar, Ria Juliani (Indonesian Journal of Advanced Research, 2025)
The expansion of oil palm plantations in Indonesia over the past two decades has significantly contributed to national economic growth, particularly in terms of foreign exchange earnings and employment. However, many plantations have been established within forest areas without valid forestry permits, creating overlapping land tenure and complex legal issues. In this research, the term forest occupation refers to the factual condition in which business actors have settled and cultivated forest areas. The inconsistency between legal maps (de jure) and field realities (de facto) has placed thousands of oil palm plantation actors, both individuals and corporations, in a “grey area” of law. To address this issue, the government enacted Law No. 6 of 2023 (Job Creation Law), which introduced Articles 110A and 110B as administrative mechanisms for legalization and fines. However, the issuance of Presidential Regulation No. 5 of 2025 introduced a new approach through the establishment of the Forest Area Enforcement Task Force (Satgas PKH) involving the military, police, and the Attorney General’s Office, with powers to evict land and impose criminal sanctions—later supported by Ministerial Decree No. 36 of 2025. This policy is considered to violate the constitutional rights of business actors and disregard the principle of lex superior derogat legi inferiori, which holds that lower regulations must not contradict higher laws. This study employs both normative and empirical legal approaches to analyze the normative conflict between regulations. The findings highlight that resolving forest occupation disputes by oil palm enterprises must prioritize the principles of legality, substantive justice, reinforcement of due process of law, and transparency through the One Map Policy to ensure legal certainty and protection for bona fide business actors.